Inclusive education in Brazil: evaluation of the results and strategies of goal 4 of the PNE (Revista Lusófona de Educação, 2025)
The present study aims to evaluate the partial results of Goal 4 of the Brazilian National EducationPlan (PNE) in the universalization of access to primary education for children and adolescents with disabilities,global developmental disorders (GDD), and high abilities/giftedness, focusing on the percentage of schoolenrollment, inclusion in regular classes, and access to Specialized Educational Assistance (SEA). This quantitative documentary analysis uses secondary data from the 2010 Demographic Census and the Basic EducationCensus (2013-2023), published by the National Institute for Educational Studies and Research Anísio Teixeira(INEP). Descriptive statistical techniques were applied to analyze the indicators of Goal 4. The results show thatfor Indicator 4A, data from 2010 indicated that 82.5% of students with disabilities were enrolled in school. By2023, Indicator 4B indicates that 95% of students were in regular classes. However, Indicator 4C reveals thatonly 47% of students received SEA in the same year, highlighting a need for more specialized support. It isconcluded that despite quantitative advances in school inclusion, the decline in SEA undermines the quality ofinclusion, highlighting the need for more significant investment in specialized support to ensure effective andequitable inclusion.Keywords: National Education Plan (PNE) - Brazil; Inclusive Education - Brazil; Public Policies - Brazil